GAMBARAN SELF ACCEPTANCE REMAJA YANG MENGALAMI FATHERLESS DI MATANI SATU KECAMATAN TOMOHON TENGAH - P. Padang, Patra; Rindengan, Mersty E.; Naharia, Melkian (PSIKOPEDIA, 2024)
This research uses a qualitative research method with a phenomenological approach. In this research, the data collection method used was interviews. Determining the subjects in this study used a purposive sampling technique, totaling 2 young people aged 21 and 22 years. This research aims to determine the picture of self-acceptance of teenagers who are orphans in Matani Satu, Central Tomohon District. The results showed that the two subjects had different self-acceptance. Subject Lisa has good self-acceptance, while subject Raisa has not fully accepted herself. The dominant factors that shape the self-acceptance of both subjects are an understanding of oneself, realistic expectations, the absence of environmental obstacles and self-perspective.